BIOLOGICAL PROPERTIES OF ANAMORPHE AND TELEOMORPHE OF THE CAUSING AGENT OF HUMAN INTERDIGITAL TRICHOPHYTHY (Experimental biology, 2022)
The article presents the results of isolation of anthropophilic strains of dermatomycetes and analysis of their biological properties. The biological properties of dermatomycetes were studied: cultural, morphological, biochemical, phenotypic and genetic identification of strains was carried out. It has been established that the T. mentagrophytes var. interdigitale No. 5 isolated from the patient's skin and affected nail was distinguished by polymorphism of cultural characters and a variety of morphological microstructures. The fungus strain T. mentagrophytes var. interdigitale No. 9 isolated from the skin of the lesion of the interdigital folds of the legs had more stable cultural and morphological characteristics. Analysis of biochemical properties revealed the presence of saccharolytic and urease activity.At the initial isolation of the culture, the anthropophilic strains were phenotypically reliably the strains of Trichophyton mentagrophytes var. interdigitale. Long-term storage of cultures by subculturing has led to the appearance of morphologically heterogeneous colonies of strains which was expressed in the appearance of pronounced wrinkling, noticeable radial grooves and zonal rings, powerful branching into the substrate and its breaks, changes in the color of the colony, changes in the pigmentation of the reverzum.As a result of the molecular genetics identification of the strain strain by analysis of the ITS region in BLAST, it was revealed that the cultures are a teleomorph of the dermatomycete T. mentagrophytes var. interdigitale known as Arthroderma vanbreuseghemii with 100% confidence.
Keywords: anamorph, teleomorph, pathogens of dermatomycosis, anthropophilic dermatomycetes, interdigital trichophytosis, arthrospores, mycelium, microconidia, macroconidia